Cold ion spectroscopy for structural identifications of biomolecules. Issue 3 (2nd October 2018) - Boyarkin, Oleg V.
ABSTRACT: Over the last decade, the spectroscopy of cryogenically cold ions isolated in the gas phase has been developed as a new tool for structural elucidations of biological molecules. Cooling allows for vibrational resolution in UV and IR spectra of small to midsize peptides, enabling different multi-laser techniques of conformer-specific spectroscopy. In conjunction with quantum chemistry calculations, IR spectra of single conformers allows for solving their intrinsic geometries. Here, we briefly review some fundamental and technical aspects of the cold-ion spectroscopy (CIS) approach and illustrate its application for protonated peptides, carbohydrates and for non-covalent complexes of biomolecules. The challenges and limitations of CIS in view of its relevance to life-science studies are critically assessed. Finally, we discuss and illustrate some approaches of CIS for the analytical identification of biomolecules, in particular the recently developed method of 2D UV-MS fingerprinting, which combines CIS with high-resolution mass spectrometry.